Light and Dark Reactions of the Uptake Hydrogenase in Anabaena 7120 - Houchins, Jeffrey P. (1981)
Reactions of the uptake hydrogenase from Anabaena 7120 (A.T.C.C. 27893, Nostoc muscorum) were examined in whole filaments, isolated heterocysts, and membrane particles. Whole filaments or isolated heterocysts that contained nitrogenase consumed H(2) in the presence of C(2)H(2) or N(2) in a light-dependent reaction. If nitrogenase was inactivated by O(2) shock, filaments catalyzed H(2) uptake to an unidentified endogenous acceptor in the light. Addition of NO(3)(−) or NO(2)(−) enhanced these rates. Isolated heterocysts consumed H(2) in the dark in the presence of electron acceptors with positive midpoint potentials, and these reactions were not enhanced by light. With acceptors of negative midpoint potential, significant light enhancement of H(2) uptake occurred. Maximum rates of light-dependent uptake were approximately 25% of the maximum dark rates observed. Membrane particles prepared from isolated heterocysts showed similar specificity for electron acceptors. These particles catalyzed a cyanide-sensitive oxyhydrogen reaction that was inactivated by O(2) at O(2) concentrations above 2%. Light-dependent H(2) uptake to low potential acceptors by these particles was inhibited by dibromothymoquinone but was insensitive to cyanide. In the presence of O(2), light-dependent H(2) uptake occurred simultaneously with the oxyhydrogen reaction. The pH optima for both types of H(2) uptake were near 7.0. These results further clarify the role of uptake hydrogenase in donating electrons to both the photosynthetic and respiratory electron transport chains of Anabaena.